Dust temperature in ALMA [C ii]-detected high-z galaxies. Issue 4 (13th March 2021) - Sommovigo, L; Ferrara, A; Carniani, S; Zanella, A; Pallottini, A; Gallerani, S; Vallini, L
ABSTRACT: At redshift z > 5, the far-infrared (FIR) continuum spectra of main-sequence galaxies are sparsely sampled, often with a single data point. The dust temperature T d, SED, thus has to be assumed in the FIR continuum fitting. This introduces large uncertainties regarding the derived dust mass ( M d ), FIR luminosity, and obscured fraction of the star formation rate. These are crucial quantities to quantify the effect of dust obscuration in high- z galaxies. To overcome observation limitations, we introduce a new method that combines dust continuum information with the overlying [C II ] 158 µm line emission. By breaking the M d – T d, SED degeneracy, with our method, we can reliably constrain the dust temperature with a single observation at 158 µm. This method can be applied to all Atacama Large Millimeter Array (ALMA) and NOEMA [C II ] observations, and exploited in ALMA Large Programs such as ALPINE and REBELS targeting [C II ] emitters at high- z . We also provide a physical interpretation of the empirical relation recently found between molecular gas mass and [C II ] luminosity. We derive an analogous relation linking the total gas surface density and [C II ] surface brightness. By combining the two, we predict the cosmic evolution of the surface density ratio Σ _H_2 / Σ _gas . We find that Σ _H_2 / Σ _gas slowly increases with redshift, which is compatible with current observations at 0 < z < 4.